Improving Students’ Critical Thinking and Communication Skill Through Blended Learning Model at University - Muhammad Darrin Zuhri; Evha Nazalatus Sya’adiyah (ELITE JOURNAL, 2023)
This study aims to investigate the effectiveness of the blended learning model in improving critical thinking and communication skills of students at university. This is a quasi-experimental study with a non-equivalent control group design involving one experimental group and one control group. The research population comprised students sitting in the English Department of Education Faculty at Madura University, who are selected purposively. The data is about critical thinking skills that will gather using a test, while the data about communication skills are obtained through observations. The data will be analyzed using a paired sample t-test and an independent sample t-test. The findings show that, first, the implementation of the blended learning model effectively increases the critical thinking skils; second, the use of the blended learning model effectively improves students’ communication skills and third, based on the independent sample t-test, students’ critical thinking skills and communication skills in the experimental class had a significant difference from those in control class. Keywords: Blended learning, critical thinking skills, communication skills